Ukrainian flora checklist. 3: families Apiaceae (= Umbelliferae), Araliaceae (Apiales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
The family Apiaceae includes more than 400 genera and from 3,500 to 4,000 species, distributed on all continents except Antarctica, with the greatest diversity in temperate latitudes and mountain systems, mainly in Europe, North America, but most often in Asia. In Ukraine, there are 74 genera and 161 species (including subspecies), of which more than half of the genera (48) are represented by only one species. Significant nomenclature changes have taken place in many genera and species. In particular, Archangelica is included in the genus Angelica; Siella erecta is fell in the genus Berula. Laserpitium alpinum is recognized as a synonym for L. krapffii, and L. hispidus and L. prutenicum are included in the new genus Silphiodaucus, isolated on the basis of molecular data. New to the flora of the region are Bilacunaria microcarpos, Bupleurum commutatum, B. testiculatum, Bifora testiculata, Cyclospermum leptophyllum, Ferulago aucheri. Significant changes have been made in the nomenclature names of a number of species and their authors. In particular, the new priority genus (and species) names are Mutellina purpurea (Ligusticum mutellina), Myrrhoides nodosa (Physocaulis nodosus). Priority names are Angelica sylvestris (A. montana), Anthriscus sylvestris (A. nemorosa), Buniun microcarpum (B. ferulaceum), Bupleurum multinerve (B. ranunculoides auct.), Cenolophium fischeri (C. denudatum), Conioselinum tataricum (C. vaginatum auct.), Palimbia rediviva (P. salsa), Scandix australis (S. taurica), Heracleum villosum (H. stevenii), H. wilhelmsii (H. mantegazzianum) and others. Significant nomenclature changes have occurred in the genus Pimpinella, which recognizes such microspecies from the aggregate complex of P. saxifraga aggr., as: P. austriasca, P. dissecta, P. hircina. Pimpinella lithophila, P. titanophila and P. tragium s. str. form a complex taxonomic aggregate, which is characterized by a wide range of variability in the dissection of the plate of basal leaves. Therefore, the concept of the only polymorphic species of P. tragium s. l. for Eastern Europe is the most reasonable within which all these taxa should be recognized as subspecies morphologically related to transitions. Segregate genera such as Cervaria, Dichoropetalum, Macroselinum, Oreoselinum have been singled out from the genus Peucedanum, but their alternative names, which are currently used for the genus Peucedanum s. l. The genus Hydrocotyle L. is included in the family Araliaceae, which is confirmed by molecular data (nucleotide sequences). The family Araliaceae has from 40 to 70 genera and from 850 to 1650 species, distributed mainly in tropical, partly in temperate latitudes; in the flora of Ukraine – two genera and three species.
Keywords: annotated list (checklist), Apiaceae, Araliaceae, distribution, flora of Ukraine.